The evening complex is central to the difference between the circadian clocks of Arabidopsis thaliana shoots and roots. Issue 3 (29th April 2020) - Nimmo, Hugh G.; Laird, Janet; Bindbeutel, Rebecca; Nusinow, Dmitri A.
Abstract : The circadian clock regulates the timing of many aspects of plant physiology, and this requires entrainment of the clock to the prevailing day:night cycle. Different plant cells and tissues can oscillate with different free‐running periods, so coordination of timing across the plant is crucial. Previous work showed that a major difference between the clock in mature shoots and roots involves light inputs. The objective of this work was to define, in Arabidopsis thaliana, the operation of the root clock in more detail, and in particular how it responds to light quality. Luciferase imaging was used to study the shoot and root clocks in several null mutants of clock components and in lines with aberrant expression of phytochromes. Mutations in each of the components of the evening complex (EARLY FLOWERING 3 and 4, and LUX ARRHYTHMO) were found to have specific effects on roots, by affecting either rhythmicity or period and its response to light quality. The data suggest that the evening complex is a key part of the light input mechanism that differs between shoots and roots and show that roots sense red light via phytochrome B.